2016
DOI: 10.1111/phn.12247
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Nurses' Activities for Suicide Prevention in Japan

Abstract: The activities of suicide prevention by PHNs included a process of developing a caring network that lead to the enhancement of the caring capacity of the community as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Although studies in various work settings, regardless of nurses' experience, considered organized and protocol-based suicide assessment important (Hu et al, 2015;Vandewalle et al, 2019aVandewalle et al, , 2019bWolf et al, 2018). Marutani et al (2016), in a study among public health nurses in the Tokyo Metropolitan area, evaluated suicides after they were committed, collecting information from the community to understand the reasons for suicide. Vedana et al (2017) performed a study set in an emergency department in Brazil, identifying that the nurses lack protocols or ways of monitoring suicide.…”
Section: Nurses' Personal Distress In Suicide Carementioning
confidence: 99%
See 2 more Smart Citations
“…Although studies in various work settings, regardless of nurses' experience, considered organized and protocol-based suicide assessment important (Hu et al, 2015;Vandewalle et al, 2019aVandewalle et al, , 2019bWolf et al, 2018). Marutani et al (2016), in a study among public health nurses in the Tokyo Metropolitan area, evaluated suicides after they were committed, collecting information from the community to understand the reasons for suicide. Vedana et al (2017) performed a study set in an emergency department in Brazil, identifying that the nurses lack protocols or ways of monitoring suicide.…”
Section: Nurses' Personal Distress In Suicide Carementioning
confidence: 99%
“…In two studies conducted at hospital mental health units, some nurses reported delving into patients' life histories, assessing suffering and trauma throughout the life cycle (Oliveira et al, 2017;Vandewalle et al, 2019b). In Marutani et al (2016), public health nurses promoted follow-up and commitment among the community through a web-based network of care and mutual aid with the aim of legitimizing suicide prevention.…”
Section: Nurses' Personal Distress In Suicide Carementioning
confidence: 99%
See 1 more Smart Citation
“…The researchers reported that between 44% and 84.5% of nurses had not received information on intervention in patients at risk of suicide (Erbuto et al, 2021; Fry et al, 2019; Ramberg et al, 2016). One study revealed that nurses were forced to plan their own strategies to manage patients at risk of suicide, because they had received no training (Marutani et al, 2016). In a systematic review examining 19 intervention studies, it was found that health professionals who had received training on intervention in patients at risk of suicide had a higher level of knowledge than those who had not, that their application skills were better, and that they felt more capable at establishing communication with patients and evaluating patients (Boukouvalas et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical standpoint, knitting is gaining popularity with the young [11] as part of the wider resurgence of interest in craft activities and has been reported to have significant therapeutic benefits in both healthy and patient populations [12] , [13] , [14] . As such it is likely that more people who come to surgery may have interests and skills in knitting or similar craft activities as a pastime or hobby.…”
Section: Discussionmentioning
confidence: 99%